On the Relationship of Cognitive Emotion Regulation, Self-Efficacy, Impulsiveness, and Social Skills with Substance Abuse in Adolescents - iran jalali; Hassan Ahadi (Drug Control Headquarters, Research and Education Office, 2016)
Objective: This study aimed to investigate the relationship of cognitive emotion regulation, self-efficacy, impulsiveness, and social skills with substance abuse among students. Method: This study was a correlational one falling into the category of descriptive designs. A total of 400 senior high school students of Shiraz (first and second grades) in the academic year 2011-12 were selected by cluster sampling method as the participants of the study. These participants responded to the scales pertaining to cognitive-emotion regulation, self-efficacy, impulsiveness, social skills, and substance abuse list (researcher made). Results: The results showed that impulsiveness and low levels social skills play a significant role in predicting substance abuse. Conclusion: The results indicated that behavioral impulsiveness, low levels of self-efficacy, lack of cognitive emotion regulation, absence of thinking and planning in responsibilities, and low levels of social skills are effective in leading students to substance abuse.